Generation of equivalent forms of operational trans‐conductance amplifier‐RC sinusoidal oscillators: the nullor approach. Issue 6 (23rd June 2014) - Senani, Raj; Gupta, Manish; Bhaskar, Data Ram; Singh, Abdhesh Kumar
Abstract : It has been shown in two earlier papers published from this study that corresponding to a given single‐operational trans‐conductance amplifier (single‐OTA)‐RC and dual‐OTA‐RC sinusoidal oscillators, there are three other structurally distinct equivalent forms having the same characteristic equation, one of which employs both grounded capacitors (GC). In this study, an earlier nullor‐based theory of generating equivalent op‐amp oscillator circuits, proposed by the first author, is extended to derive equivalent OTA‐RC circuits which discloses the existence of an additional number of equivalent forms for the same given OTA‐RC oscillators than those predicted by the quoted earlier works, and thereby considerably enlarging the set of equivalents of a given OTA‐RC oscillator. Furthermore, the presented nullor‐based theory of generating equivalent OTA‐RC oscillators results in three additional interesting outcomes: (i) the revelation that corresponding to any given OTA‐RC oscillator there are two 'both‐GC' oscillators (and not merely one, as derived in the quoted earlier works); (ii) the availability of explicit current outputs in several of the derived equivalents and (iii) the realisability explicit‐current‐output 'quadrature oscillators' in some of the generated equivalent oscillators. The workability of the generated equivalent OTA‐RC oscillators has been verified by SPICE simulations, based on CMOS OTAs using 0.18 µm CMOS technology process parameters, and some sample results are given.